Duolingo in Basic English Learning: Student Engagement and Achievement - Rizki Nurhidayah Sitompul (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study investigated the effectiveness of the Duolingo app in supporting Basic English learning and examined its impact on student engagement and academic achievement. The study was conducted with a group of first-semester students over a five-month period. During this time, quantitative and qualitative data were collected through pre-tests, post-tests, classroom observations, and monitoring of student interactions with the app. The findings indicated significant improvements in students' basic English competencies, particularly in vocabulary mastery, grammar recognition, and reading comprehension. Students demonstrated greater motivation, consistency, and independence in their learning processes, largely due to Duolingo’s gamified features such as rewards, levels, and interactive exercises. These results align with the researchers' field observations, which revealed that many first-semester students at the Islamic University of North Sumatra initially had limited English proficiency, especially in vocabulary and basic sentence structure. The integration of Duolingo into regular learning activities proved highly effective in addressing these gaps, offering an accessible and learner-friendly platform that complements traditional face-to-face instruction. Overall, this study suggests that Duolingo can serve as a valuable supplementary tool in basic English teaching, particularly for beginner-level students, and recommends its broader application in similar educational contexts, as it can provide a strong foundation for English vocabulary development among novice learners.